Development of SCARLIGHT (Stand Camera Magnifier Light) Media for Improving the Seeing Ability of Low Vision - Damastuti, Eviani; Utomo, Utomo; Sulistiyana, Sulistiyana (Department of Special Education, 2024)
Experienced limitations in visual function and low vision This results in limitations in the level and diversity of visual experience. Information is obtained comprehensively through the sense of sight, therefore vision is hampered by students' low vision creating a need for learning in students' low vision in terms of educational accessibility. One of the efforts is to provide learning media that adapts to children's needs and vision. This research will develop learning mediaSCARLIGHT(Stand Which. equipped with a camera, magnifier, and lights that will be connected to a PC (Personal Computer) so that it can make it easier for teachers to teach children with low vision. The method used in this research is research and Development with ADDIE type (Analysis, design, Development, Implementation, and Evaluation). The research location is SLB A Negeri 3 Martapura. Data collection techniques using tests, interviews, and documentation. The research subjects were 6 students with low vision. Results of research into the development of SCARLIGHT Media (Stand Camera Magnifier Light) which is a shaped Stand Camera whose height can be measured according to the student's reading distance requirements vision, and the camera can be adjusted for magnification and focus and is equipped with a light that can be adjusted from dim to bright. The response results from 6 low vision students using SCARLIGHT Media stated that it helped them see objects, helped them read, see colors, and helped them display information or images in their entirety (graphs, tables, maps).